A planktonic diatom displays genetic structure over small spatial scales. (23rd April 2018) - Sefbom, Josefin; Kremp, Anke; Rengefors, Karin; Jonsson, Per R.; Sjöqvist, Conny; Godhe, Anna
Summary: Marine planktonic microalgae have potentially global dispersal, yet reduced gene flow has been confirmed repeatedly for several species. Over larger distances (>200 km) geographic isolation and restricted oceanographic connectivity have been recognized as instrumental in driving population divergence. Here we investigated whether similar patterns, that is, structured populations governed by geographic isolation and/or oceanographic connectivity, can be observed at smaller (6–152 km) geographic scales. To test this we established 425 clonal cultures of the planktonic diatom Skeletonema marinoi collected from 11 locations in the Archipelago Sea (northern Baltic Sea). The region is characterized by a complex topography, entailing several mixing regions of which four were included in the sampling area. Using eight microsatellite markers and conventional F ‐statistics, significant genetic differentiation was observed between several sites. Moreover, Bayesian cluster analysis revealed the co‐occurrence of two genetic groups spread throughout the area. However, geographic isolation and oceanographic connectivity could not explain the genetic patterns observed. Our data reveal hierarchical genetic structuring whereby despite high dispersal potential, significantly diverged populations have developed over small spatial scales. Our results suggest that biological characteristics and historical events may be more important in generating barriers to gene flow than physical barriers at small spatial scales.